2021
DOI: 10.1177/00307270211058209
|View full text |Cite
|
Sign up to set email alerts
|

Yam seed system characteristics in Nigeria: Local practices, preferences, and the implications for seed system interventions

Abstract: Yam is an important food and cash crop in Nigeria. The seed system is mostly farmer-based and its challenges and opportunities are not well documented. This study reports results of surveys, interviews, focus group discussions and participant observations that describe local practices characterizing yam cultivation and the farmer-based seed system in five states in Nigeria. Our findings show that ware and seed yam are dynamic and highly commercialized goods in Nigeria. There is a high demand for, and a high tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In contrast, the low variation within cluster revealed a low degree of genetic differentiation, which may be attributed to regional preferences for some dominant varieties ( Bakayoko et al., 2021 ). As stated by Stuart et al. (2021) , sharing (small amounts) of seed-yam tubers as a gift is a common practice among farmers of the same and or different communities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the low variation within cluster revealed a low degree of genetic differentiation, which may be attributed to regional preferences for some dominant varieties ( Bakayoko et al., 2021 ). As stated by Stuart et al. (2021) , sharing (small amounts) of seed-yam tubers as a gift is a common practice among farmers of the same and or different communities.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies [50,51] have also reported the high importance yet low commercialization level in yam with households selling less than 23% of the output as ware yam. It is of interest to note that despite Nigeria's ranking as a top world producer of yam contributing up to 71% to world output of yam the country does not feature among the top ten exporting countries in the global yam market [52] [53,54].…”
Section: Commercialization Index Along Key Crops In the Study Areamentioning
confidence: 99%
“…It is noteworthy that yam farmers can only capture the benefit of the genetic gains from breeding programs when seed systems are well-functioning (Mausch et al, 2021;Stuart et al, 2021;Kalu et al, 2023). Stakeholders, especially seed multipliers, should be trained on how to rapidly multiply seeds.…”
Section: Improving Yam Production and Use In Eastern Drc Would Requir...mentioning
confidence: 99%